USING MODERN TECHNOLOGIES IN ORGANIZING MUSIC LESSONS - Mansur Mamirov (Web of Journals Publishing, 2024)
Information is given on ways to effectively use information and communication technologies when organizing classes with students studying music.
Keywords: Music, information technologies, methodology, education, lesson, training.